2009
DOI: 10.1007/s10552-009-9365-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and type distribution of human papillomavirus in 5,000 British Columbia women—implications for vaccination

Abstract: Background Human papilloma virus (HPV) prevalence studies performed in different regions and population groups across Canada would inform public health decisions regarding implementation of anti-HPV vaccines. Methods A total of 8,700 liquid-based specimens from 8,660 women aged 13-86 from throughout British Columbia were collected. DNA was isolated from 4,980 of these samples and assessed for HPV prevalence and type distribution. HPV was detected by PCR analysis using tagged GP5?/6? consensus primers to amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
35
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 28 publications
12
35
2
2
Order By: Relevance
“…The assessment of HPV prevalence by age group revealed a higher prevalence in the younger age groups, which is consistent with the results of other studies [27,28,36,37]. This finding confirms what is already known about the natural history of HPV infection, which is characterized by higher infection rates after sexual initiation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The assessment of HPV prevalence by age group revealed a higher prevalence in the younger age groups, which is consistent with the results of other studies [27,28,36,37]. This finding confirms what is already known about the natural history of HPV infection, which is characterized by higher infection rates after sexual initiation.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to most European studies, the two most common HPV types detected in NWT were HPV16 and 31 [29][30][31][32]. The HPV16/18 prevalence in the NWT was lower than that observed in all similar studies in Canada [26][27][28] but was comparable to the prevalences observed in studies in Europe and the US [31,[33][34][35]. Several HR-HPV types other than HPV16/18, such as HPV31, 66, 39, 51 and 62, are relatively common in the NWT.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…15,16 Although comparisons are difficult because of the small number of young women, the age-specific curve of HPV prevalence in Algeria appeared to differ somewhat from the steep decrease seen after age 25 years in high-resource countries 17 and more to resemble the flat age curves reported previously in some low-resource countries in Asia and Africa. 4,14,17 There was even a suggestion (albeit not significant) that HPV prevalence might be higher in older generations of women.…”
Section: Discussionmentioning
confidence: 60%